The Influence of Workplace Spirituality in Engagement, Resilience and Efficacy of Secondary Teachers in Iba District, Schools Division of Zambales - Fulgencio, Shiela Marie R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examined the relationship between workplace spirituality and engagement, resilience, and self-efficacy among secondary school teachers in Iba District, Schools Division of Zambales, during the 2018-2019 school year. A descriptive research design was used, employing a questionnaire to gather data from 138 randomly selected teachers. The study explored workplace spirituality through compassion, meaningful work, mindfulness, and transcendence, alongside teacher attributes such as engagement, resilience, and self-efficacy. It also considered respondents' age, sex, religion, civil status, educational attainment, and years of service. Findings revealed that most respondents were 33 years old, female, Catholic, married, held a BS degree with MA units, and had seven years of teaching experience. Workplace spirituality, particularly compassion, mindfulness, and transcendence, was perceived as occurring "often," while meaningful work was rated as "always." Teachers consistently rated their engagement, resilience, and self-efficacy as "always" present. Significant differences were found in workplace spirituality and teacher attributes when grouped by demographic variables. A very high correlation existed between workplace spirituality and teacher attributes. The study recommends home visits to support students, encouraging teachers to develop empathy and apply moral values. Schools should provide training on compassion, mindfulness, and transcendence. Further research is suggested to validate these findings.